Implikatur Dalam Tuturan Komedi Tunggal Yang Dibawakan Mo Sidik Pada Acara Bali Comedy Club - Khairunnisa, Salwa (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2023)
This study aims to describe the implications of speech in a single comedy hosted by Mo Sidik at the Bali Comedy Club event. In this study using the theory of implications according to Horn and (2012)Huang (2014). The research method used in this study is a descriptive qualitative method where researchers focus on discussing speech data contained in the single comedy delivered by Mo Sidik. Based on the results of the analysis, it was found that the single comedy material delivered by Mo Sidik contained conventional implications, especially in the punchline of the jokes he told. The jokes told by Mo Sidik tell a lot about his anxiety about government policies and his social life which has a fat body.